RELATIONSHIP BETWEEN SELF-REGULATION SKILLS AND ACADEMIC ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS IN PHYSICS IN AWKA EDUCATION ZONE (UNIZIK Journal of STM Education, 2025)
This study examined the relationship between self-regulation skills and academic achievement ofsecondary school students in Physics in Awka Education Zone of Anambra State. The study wasguided by tworesearch questions and two null hypotheses were tested at 0.05 level of significance.The study adopted a correlation research design. The population of the study consisted of 2532secondary school two (SS 2) students offering Physics from all the public secondary schools inthe zone. Multi-stage sampling procedure was used to draw 345 secondary school two (SS 2)students from the population. The instruments used for data collection included; Physics SelfRegulation Questionnaire (PSRQ) and average scores of students for 2024/2025 academic session.The instruments PSRQ was validated by three experts, two from the Department of ScienceEducation and one from Department of Educational Foundations (Measurement and Evaluationunit), all in Nnamdi Azikiwe University, Awka. The reliability of the instrument was establishedusing Cronbach's alpha method, with coefficient of 0.86 for PSRQ, indicating satisfactory internalconsistency. Data collection was done through direct administration of the questionnaire torespondents by the researcher and research assistants who are secondary school Physics teachers.Pearson product moment correlation was employed for the analysis of the data collected usingStatistical Package for Social Sciences (SPSS, vs 27). The findings of the study revealed that thereis a moderate positive and significant relationship between self-regulation skills scores andacademic achievement scores of secondary school students in Physics. In addition, the studyshowed that there is moderate positive and significant relationship between self-regulation skillsscores and academic achievement scores for both male and female secondary school students inPhysics in Awka Education Zone. Based on the findings, the study concluded that self-regulationskills play a crucial role in enhancing students’ academic achievement in Physics. It wasrecommended amongst others that Physics teachers should deliberately incorporate strategiessuch as goal setting, self-planning, self-monitoring, and self-reflection into classroom activities tostrengthen students’ self-regulation skills, which have been shown to significantly enhanceacademic achievement.
Keywords: Self-regulation skills, Physics, Academic achievement, Gender, Secondary School